Synthesis and structure-activity relationships of cerebroside analogues as substrates of cerebroside sulphotransferase and discovery of a competitive inhibitor. (1st January 2020) - Li, Wenjin; Guillaume, Joren; Baqi, Younis; Wachsmann, Isabell; Gieselmann, Volkmar; Van Calenbergh, Serge; Müller, Christa E.
Abstract: Metachromatic leukodystrophy (MLD) is a rare genetic disease characterised by a dysfunction of the enzyme arylsulphatase A leading to the lysosomal accumulation of cerebroside sulphate (sulphatide) causing subsequent demyelination in patients. The enzyme galactosylceramide (cerebroside) sulphotransferase (CST) catalyses the transfer of a sulphate group from 3′-phosphoadenosine-5'-phosphosulphate (PAPS) to cerebrosides producing sulphatides. Substrate reduction therapy for arylsulphatase A by inhibition of CST was proposed as a promising therapeutic approach. To identify competitive CST inhibitors, we synthesised and investigated analogues of the substrate galactosylceramide with variations at the anomeric position, the acyl substituent and the carbohydrate moiety, and investigated their structure–activity relationships. While most of the compounds behaved as substrates, α-galactosylceramide 16 was identified as the first competitive CST inhibitor. Compound 16 can serve as a new lead structure for the development of drugs for the treatment of this devastating disease, MLD, for which small molecule therapeutics are currently not available.